H 2 gas sensor based on PdO x -doped In 2 O 3 nanoparticles synthesized by flame spray pyrolysis - Kanittha Inyawilert (2019)
© 2018 Elsevier B.V. In this work, 0–1.0 wt% PdO x -doped In 2 O 3 nanoparticles were successfully synthesized by flame spray pyrolysis (FSP) in a single step for the first time and investigated for gas-sensing applications. The sensing films were fabricated by spin coating and tested towards hydrogen (H 2 ) at various temperatures ranging from 150 to 350 °C in dry air. The powder and sensing film properties were analyzed by X-ray analyses, nitrogen adsorption and electron microscopy. The spherical and cubic In 2 O 3 nanoparticles with diameters ranging from 2 to 20 nm were observed with no apparent secondary phase of Pd or PdO x . Detailed analyses suggested that Pd species might be in the form of PdO x crystallites embedded in and on grain boundaries of In 2 O 3 nanoparticles. From gas-sensing measurements, hydrogen-sensing characteristics of In 2 O 3 nanoparticles were significantly improved by PdO x doping particularly at the optimal Pd content of 0.50 wt%. The optimal PdO x -doped In 2 O 3 sensing film showed a high response of 3526 towards 10,000 ppm H 2 at the optimal working temperature of 250 °C. In addition, PdO x doped In 2 O 3 sensing films displayed good stability and high H 2 selectivity against various toxic and flammable gases including H 2 S, NO 2 , C 2 H 4 O, C 2 H 4 , C 2 H 5 OH and C 2 H 2 .